AT-303:Comparison of Sago and Sweet Sorghum for Ethanol production using Saccharomyces Cerevisiae - Kamaruddin, Mohd Hider; Nadir, Najiah; Mel, Maizirwan; Abdulkarim, Mohd Ismail (2012)
There is a growing interest in the application of bioethanol as biofuel since it has the possibility to be the potential substitute for fossil fuel. Selection of the best raw material for ethanol production is crucial for the substrate preparation. High amount of starch content is one of the important criteria in choosing the best suitable crop for bioethanol production. Two types of starchy crops, Sago and Sweet Sorghum are considered to have a high potential as an energy crop. The two-step enzymatic hydrolysis of sago and sweet sorghum were performed by commercially available α-amylase and glucoamylase enzyme. Further ethanol batch fermentation by Saccharomyces cerevisiae strain from the obtained hydrolysates of sago and sweet sorghum were studied. For both sago and sweet sorghum, the hydrolysis and fermentation were done in a 2 L stirred tank bioreactor, B-Braun fermenter, using the same process conditions. Each running was completed within 72 hours. The amount of glucose obtained after hydrolysis process was greater in sweet sorghum compared to sago, which are 50.07 and 48.7 g L-1, respectively. The amount of ethanol concentration also higher for sweet sorghum compared to sago at the 72 h fermentation process, which are 40.11 and 26 g L-1, respectively.